METAMORPHIC EVOLUTION OF LATE PRECAMBRIAN ECLOGITES AND ASSOCIATED METABASITES, GORNY ALTAI, SOUTHERN RUSSIA - Ota T.; Buslov M.M.; Watanabe T. (My University, 2002)
In the Vendian-Cambrian orogenic belt of the Chagan-Uzun and Kurai areas, Gorny Altai, high-pressure, low-temperature (HP/LT) metabasites and associated schists comprise a metamorphic complex less than 2 km thick. The Chagan-Uzun metabasites occur as lenticular intercalations in a recrystallized serpentinite. They include eclogite, garnet-amphibolite, amphibolite, and lower-grade schist; the first two contain glaucophane in the strict sense. The Kurai metabasites occur as a coherent body with intercalations of calcareous and siliceous schists. They are divided into four mineral zones: actinolite, hornblende, garnet-barroisite, and garnet-hornblende, based on mineral assemblages. Their metamorphic grade corresponds to greenschist to epidote-amphibolite facies, and decreases from the garnet-hornblende zone in the central part of the body to the actinolite zone in the western and eastern margins through the garnet-barroisite and hornblende zones.
Keywords: Cambrian; Vendian; Paleozoic::Cambrian; Докембрий::Протерозой::Неопротерозойская::Вендский; Precambrian::Proterozoic::Neoproterozoic::Vendian; Палеозой::Кембрийская